Tissue clonality of dendritic cell subsets and emergency DCpoiesis revealed by multicolor fate mapping of DC progenitors - Cabeza-Cabrerizo, Mar (Sci Immunol, 2019)
Conventional dendritic cells (cDCs) are found in all tissues and play a key role in immune surveillance. They comprise two major subsets, cDC1 and cDC2, both derived from circulating precursors of cDCs (pre-cDCs), which exited the bone marrow. We show that, in the steady state mouse, pre-cDCs entering tissues proliferate to give rise to differentiated cDCs, which themselves possess residual proliferative capacity. We use multi-colour fate mapping of cDC progenitors to show that this results in clones of sister cDCs, most of which comprise a single cDC1 or cDC2 subtype, suggestive of pre-cDC commitment. Upon infection, a surge in the influx of pre-cDCs into the affected tissue dilutes clones and increases cDC numbers. Our results indicate that tissue cDCs can be organized in a patchwork of closely positioned sister cells of the same subset whose co-existence is perturbed by local infection, when the bone marrow provides additional pre-cDCs to meet increased tissue demand.